PENGEMBANGAN WILAYAH PESISIR TIMUR KOTA TARAKAN BERDASARKAN SARANA DAN PRASARANA - Prihartanto, Eko (Journal of Research and Technology, 2020)
Tarakan City is an island that has a coast and as the largest city located in North Kalimantan Province which makes tourism as one of the main sectors. Regional development is carried out to determine community needs in the future. This study used quantitative and descriptive qualitative data analysis research using a scalogram analysis to determine the location of growth centres based on the availability of facilities and infrastructure of each region's infrastructures. Based on the analysis of the scalogram showed the hierarchy area by the division of the category based on facilities and infrastructures in the northern coastal area of ​​the Tarakan city.